Tissue engineering practices and the issue of “playing God”: a yheological exposition - Mohd. Azharuddin, Nur Syamimi; Ahmad Radzi, Muhammad Aa'zamuddin; Azhim, Azran; Sha'ban, Munirah; Hashi, Abdurezak Abdulahi; , (2018)
Over the years, the modern scientific discoveries have been introduced, if not reproached, with the term “playing God”, particularly in the emerging and growing field of biomedical and biotechnology researches. Primarily, the term was pointed at the activities of end-of-life decisions among healthcare personnel and only in the recent times the term made into the theological discussion involving various technologies produced by mankind, including tissue engineering. Often the critics aim to demonstrate how certain approaches of science transgress the limits of man and cross fixed boundaries establishing a certain order in the natural world. There are very little discussions, if any, regarding the concepts of tissue engineering from the view of Islamic theology, particularly on the issue whether the attempt of reconstructing or regenerating human body part substitutes equals to the mortal man taking the roles, functions or tasks of God. Islam, as a way of life, welcomes any efforts for the betterment of mankind. This is based on the driven values of life preservation and harm reduction. Islam believes that the power to create things out of nothing, creatio ex nihilo, belongs to the Almighty God alone whilst the act of man reconstructing functional organs or tissues in tissue engineering field is a different form of creation. Man recreates something out of something else while God creates something from nothing. The authors thanked the Kulliyyah of Allied Health Sciences, International Islamic University Malaysia (IIUM), Kuantan Campus, and Tissue Engineering and Regenerative Medicine Research Team, IIUM for their support. The authors also expressed their gratitude to Ministry of Higher Education of Malaysia for providing Transdisciplinary Grant Scheme TRGS16-02-003-0003.